Additions to clay bodies - Standen, Kathleen (The new ceramics, 2013)
"Beginning with an introduction to collecting local clay and making your own clay bodies, the book moves on to cover the array of additions being used by artists today, from hard materials like stones, glass and rust, to combustible matter and fibre, metals including wire and mesh, and colour in various forms."--Back cover.